The Giraffe and the pelly and me - Roal Dahl (UK Puffin books, 2013)
This is a fun and imaginative story about a young boy named Billy, who dreams of owning a sweet shop. One day, he discovers that the abandoned building near his home has been taken over by a strange group: a Giraffe, a Pelican (Pelly), and a Monkey. Together, they run a window-cleaning company called The Ladderless Window-Cleaning Company$1 (Bbecause the Giraffe$1 (Bs long neck replaces the need for ladders, and the Pelican uses his big beak to carry water. Billy becomes friends with them and joins them on a job to clean the windows of Hampshire House, owned by the wealthy Duke of Hampshire. During the job, they catch a burglar attempting to steal valuable jewels. As a reward, the Duke gives them a new home on his estate and helps Billy open his dream sweet shop.s